Terrorism in the Paradigm of Modern Conflicts - Zhetpisbayeva, B (Public Administration and Civil Service, 2016)
The article deals with the problems of countering terrorism, the place of the phenomenon in the paradigm of modern conflicts that shake the world. Particular attention is paid to religious terrorism as one of the extremely dangerous and hard forms of violence.